Trampantojo : el arte del engaño - camuflaje corporal - Salas Acosta, Luz Marina (2019)
The concept of camouflage in art is incorporated as disappearance, invisibility, ambiguity, ambivalence... mimicry, distortion, rupture, fragmentation, coincident... hiding or highlighting the inclusion body to support coded, employed by several artists as a expression is the common denominator in the quest to pass as real what is only fiction